2022
DOI: 10.20961/jphystheor-appl.v6i1.59142
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Manganit Analysis Based on La0.7Ca0.3Mn1-xTixO3 (x=0, 0.1, 0.2, and 0.3) as Potential Microwave Absorber Material with Sol-Gel Method

Abstract: <p>Electromagnetic wave is an energy flow in the form of electric and magnetic field as the technology development causes electromagnetic wave exposure level changes significantly and resulting an electromagnetic wave radiation that leads bad impacts on human health. In this case, manganite perovskite became an interesting topic of study that aims to produce material engineering to obtain a material with the best property as absorber. This study is based on lanthanum manganite La<sub>0.7</sub>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Conversely, x = 0.1 exhibits crystal and particle size variations relative to the others. While several studies employing the same synthesis method report the existence of similar impurities [6,14,15,24], the VNA data compellingly highlights the influence of x doping. Table 5 highlights reflection loss values for distinct perovskite materials.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Conversely, x = 0.1 exhibits crystal and particle size variations relative to the others. While several studies employing the same synthesis method report the existence of similar impurities [6,14,15,24], the VNA data compellingly highlights the influence of x doping. Table 5 highlights reflection loss values for distinct perovskite materials.…”
Section: Resultsmentioning
confidence: 82%
“…Chen et al demonstrated that LaTiO3 exhibits a high dielectric constant when substituted with Mn at site A [13]. Subsequent research indicated that replacing Ti at site B in LaMnO3 results in a high dielectric constant [13][14][15]. Fira et al synthesized La0.7Ca0.3Mn1-xTixO3 materials (x = 0, 0.1, 0.2, and 0.3), noting the highest Reflection Loss (RL) value when x = 0.3, registering RL -10.07 dB at a frequency of 10.4 GHz, corresponding to microwave absorption of approximately 90.16% [16].…”
Section: Introductionmentioning
confidence: 99%